Effect of tool rotation direction, pin overlap, and pin shape on material flow in one-step double-acting friction stir welding of stainless steel: A Modeling study - Eko Prasetya Budiana; Rian Firmanda; Essam R. I. Mahmoud; Triyono (Universitas Muhammadiyah Magelang, 2026)
Stainless steel is widely used in various industrial applications due to its excellent corrosion resistance and mechanical strength. However, conventional fusion welding of stainless steel often leads to several problems such as hot cracking, sensitization caused by chromium carbide precipitation, and large thermal distortion. Friction Stir Welding (FSW), a solid-state joining technique, has been developed to overcome these limitations by producing high-quality joints without melting the base material. Nevertheless, welding thick plates using conventional FSW frequently results in incomplete penetration. To address this limitation, a One-Step Double-Acting Friction Stir Welding (DA-FSW) technique is proposed, in which two tools operate simultaneously from the top and bottom surfaces of the workpiece. In this study, material flow behavior and heat distribution during DA-FSW of stainless steel are investigated using Computational Fluid Dynamics (CFD) simulation. The model considers variations in pin geometry (cylindrical, conical, triflate, and tapered triflate), tool rotation direction, and pin overlap. Stainless steel is modeled as a non-Newtonian fluid to represent its plasticized behavior under frictional heating. The simulation results show that complex pin geometries such as tapered triflate produce up to 15–20% higher material flow velocity and generate a more uniform temperature distribution (approximately 5–10% variation across the stir zone) compared with simple cylindrical pins. Furthermore, opposite tool rotation directions improve material mixing and reduce temperature gradients, while an optimal pin overlap increases heat generation by approximately 12%, leading to more stable material flow. These results demonstrate that the combination of complex pin geometry, opposing rotation direction, and appropriate pin overlap significantly improves thermal distribution and material flow stability, which are essential for achieving defect-free welds in thick stainless steel plates.